PENGUATAN KINERJA PEMASARAN MELALUI PENGEMBANGAN INOVASI DAN KREATIVITAS PROGRAM KERJA PADA WIRAUSAHA MUDA DI SEMARANG - Sijabat, Rauly (Master of Management Diponegoro University, 2017)
Marketing performance is related to the results achieved by the company. A review of previous studies conducted leads that marketing performance can be achieved by building the capabilities of business networks created through innovation and creativity of marketing programs. These findings are then directing this research in providing empirical evidence related to the influence of innovation variables, marketing program creativity, business network capabilities and marketing performance. The data required in this study was obtained through interviews using a questionnaire on a scale of 1-7. The data obtained were analyzed by using Multiple Regression Test. The results of multiple regression testing indicate that the innovation and creativity of marketing programs proved to have a significant positive impact on business network capabilities as well as innovation, creativity of marketing programs and business network capabilities proved to improve marketing performance.